Rickettsial neglected zoonoses: prevalence of scrub typhus at central Karnataka - C. S., Vinod Kumar; Patil, Satish; Prasad, B. S.; Kalappanavar, N. K.; Jayaraj, S. G.; K., Niranjan; Jayaprakash, Roopa; K. G., Raghu Kumar; K. G., Basavarajappa; V. L., Jayasimha (International Journal of Research in Medical Sciences, 2017)
Background: Fever of unknown Origin (FUO) has many multiple causes such as enteric fever, malaria, dengue, tuberculosis, brucellosis. But scrub typhus is less known cause in Indian scenario. The present study reports the prevalence of scrub typhus at central Karnataka and compares the sensitivity and specificity of Weil-Felix test and the IgM ELISA in the detection of infection. Methods: 368 serum samples of FUO cases were collected. Weil-Felix test was performed and also analyzed for IgM antibodies to Orienta tsutsugamushi by IgM ELISA test along with haematological and biochemical investigations. Results: Out of 368 patients of fever of unknown origin, 94 cases were positive by OXK antigens by Weil Felix test and 61 were positive by ELISA test for ST IgM antibodies. Fever was the most common clinical presentation occurring in ST IgM ELISA positive cases, followed by myalgia in 90.1% cases, headache in 77%, hepatomegaly in 65.5%, splenomegaly in 62.2% and rashes were seen in 29.5% patients. Eschar was seen in 13.1% patients, pneumonia in 3.2% and meningo-encephalitis in 1.6%. Sensitivity and specificity of WFT in relation to IgM ELISA at a titre of 160 was 81.97% and 85.67% respectively. Conclusions: With the growing number of cases detected in India, scrub typhus is fast emerging as a public health threat and also due to limited diagnostics leading to underreporting, Weil Felix test could be used in adjunct with Enzyme-linked immunosorbent assay and blood parameters in the diagnosis of rickettsial diseases.